NbCl5-Promoted Synthesis of Fluorescein Dye Derivatives: Spectroscopic and Spectrometric Characterization and Their Application in Dye-Sensitized Solar Cells - da Silva, Bruno Henrique Sacoman Torquato [UNESP]; Bregadiolli, Bruna Andressa [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP]; da Silva-Filho, Luiz Carlos [UNESP] (Wiley, 2017)
Fluorescein has several applications owing to its properties, such as high molar absorptivity, high fluorescence quantum yield, high photostability, and wavelengths of absorption and emission in the visible region. The syntheses of fluorescein derivatives between phenol and anhydride derivatives by using NbCl5 as a Lewis acid is described. The products have high yields and short reaction times are observed. The study of the UV/Vis and fluorescence spectra of these derivatives and their application in dye-sensitized solar cells is also described.
Keywords: dyes/pigments; energy conversion; multicomponent reactions; niobium; sensitizers